Beyond the fixity of drawing: pictorical representation and visual narrative in graphic humor - Picado, Benjamim (2013)
We intend to examine the relationships between the representation of actions and the fixed forms of designs, departing from a look upon the narratives potentialities of visual aspects of traditional daily strips: we are especially concerned with the complementarity between the stylistic traits of caricature - as a matrix for the design of characters – and the very narrative structure of visual gags – as a privileged model for the representation of actions proper to the comedic genres of narratives. In this perspective, the morphology of visual humor – symbolized by caricature – is best addressed once their humorous grace is considered as a part of the general problem of a "lacunar" mor "experssive" style of pictorial representation: the association of such a style with a poetic approach towards laughter in caricature is instrumental to the achievement of visual narrative.